The effect of liquidity, leverage, capital intencity and profitability toward tax aggresiveness - Siska Dewi Novitasari; Eko Madyo Sutanto; Faiz Rahman Siddiq (Profesional Muda Cendekia Publishing, 2022)
The purpose of this study is to analyze the effect of liquidity, leverage, capital intensity, and profitability on tax agressiveness to mining sector companies. This type of research is quantitative research. The method of taking sample research using purposive sampling method. The writer analyze the data used classic assumption test and multiple linear regression analysis as a method on SPSS 21 program. The sample used in this study is 14 mining companies listed on the Indonesia Stock Exchange in 2015-2019, so that the overall sample is 68 which is ready to be processed. The result of the study show that liquidty variable and leverage is not affected on tax agressiveness, while the the capital intensity has a positive effect on tax agressiveness, and profitability has a negative effect on tax aggressiveness.